2017
DOI: 10.1055/s-0037-1599236
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Fitness in Children and Adolescents with Epilepsy (EpiFit)

Abstract: The objective of this study was to evaluate the correlation between fitness and health-related quality of life (HRQoL) in children with idiopathic epilepsy compared with a healthy matched control group. In this study, 107 children conducted a 6-minute walk test, anthropometric parameters were measured, and HRQoL was assessed using a standardized questionnaire (KINDL-R). Children were divided into two groups: (1) the patient group ( = 48) and (2) the healthy control group ( = 59). HRQoL of children with focal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…In conclusion, physical exercise and KD has a positive effect on epilepsy and is associated with reduced epileptic form discharges and increased seizure threshold, and seizures are unlikely to occur during incremental physical effort to exhaustion (Rauchenzauner et al, 2017). These findings are strengthened by studies in animal models of seizures and epilepsy, in which aerobic exercise training was found to retard the epileptogenic process, to reduce seizure frequency, and to promote favourable plastic changes in the hippocampus (Olivares et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In conclusion, physical exercise and KD has a positive effect on epilepsy and is associated with reduced epileptic form discharges and increased seizure threshold, and seizures are unlikely to occur during incremental physical effort to exhaustion (Rauchenzauner et al, 2017). These findings are strengthened by studies in animal models of seizures and epilepsy, in which aerobic exercise training was found to retard the epileptogenic process, to reduce seizure frequency, and to promote favourable plastic changes in the hippocampus (Olivares et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, individuals with epilepsy have low levels of maximal oxygen uptake and cardiorespiratory fitness and reduced levels of strength and flexibility. The lower aerobic fitness observed in people with epilepsy may be associated with their sedentary habits (Rauchenzauner et al, 2017). Physical activity should be encouraged in this group, as previous studies have reported several positive effects of physical exercise in people with epilepsy.…”
Section: Review Papermentioning
confidence: 90%
“…Актуальность исследования прогноза, исходов и, в части случаев, эволюции ГЭ обусловлена пожизненным течением большинства синдромов с влиянием на качество жизни пациента, непосредственно приступов, когнитивных нарушений в структуре синдрома или социальных факторов, обусловленных стигматизацией, коморбидными тревожным и депрессивным расстройствами, ограничением в учебе, вождении транспорта, трудоустройстве [18][19][20][21][22][23]. Данные аспекты остаются малоизученными в настоящий момент именно с точки зрения эволюции, в т. ч. в развитых странах.…”
Section: клинические случаи / Case Studiesunclassified